Пошаговое объяснение:
1. x+5-2(4-x)-x-4 = x + 5 - 8 + 2x - x - 4 = 2x - 7
2.4(y+4)-5(2-y)-(5+4)y-3 = 4y + 16 - 10 + 5y - 9y - 3 = 3
3.3(b+4)-3(5-b)-b-3 = 3b + 12 - 15 + 3b - b - 3 = 5b - 6
4. (k+3)-(2-k)-(1+4)k-2 = k + 3 - 2 + k - 5k - 2 = -3k - 1
5.3(m+5)-4(5-m)-(4+3)m-1 = 3m + 15 - 20 + 4m - 7m - 1 = -6
6. 3(d+2) -4(1-d)-d-4 = 3d + 6 - 4 + 4d - d - 4 = 6d - 2
7. 4(f+2)-4(2-f)-(4+4)f-3 = 4f + 8 - 8 + 4f - 8f - 3 = - 3
8. 5(a+3)-3(1-a)-a-3 = 5a + 15 - 3 + 3a - a - 3 = 7a + 9
9.2(t+4) -4(2-t)-(442)t-1 = 2t + 8 - 8 + 4t - 442t - 1 = -436t - 1
10. 4(n+1) - (5-n)-n-3 = 4n + 4 - 5 + n - n - 3 = 4n - 4
Пошаговое о1) 2(3x + 1) - x ≤ 3(x + 4), 2) 7x + 4(x - 2) > 6(1 + 3x),
6х + 2 - х ≤ 3х + 12, 7х + 4х - 8 > 6 + 18x,
5х + 2 ≤ 3х + 12, 11x - 8 > 6 + 18x,
5х - 3х ≤ 12 - 2, 11x - 18x > 6 + 8,
2х ≤ 10, -7x > 14,
х ≤ 5, x < - 2,
х ∈ (-∞; 5]; x ∈ (-∞; -2);
3) 2(x - 1) - 3(x + 2) < 6(1 + x), 4) 7(y + 3) - 2(y + 2) ≥ 2(5y + 1),
2x - 2 - 3x - 6 < 6 + 6x, 7y + 21 - 2y - 4 ≥ 10y + 2,
-x - 8 < 6 + 6x, 5y + 17 ≥ 10y + 2,
-x - 6x < 6 + 8, 5y - 10y ≥ 2 - 17,
-7x < 14, -5y ≥ -15,
x > -2, y ≤ 3,
x ∈ (-2; +∞); y ∈ (-∞; 3]. бъяснение:
2) 21/8×24/1=21×24/8×1=63
3) 11/8÷(-3 3/4)=11×(-4)/8×36=(- 11/72)
4) (- 11/72)+63=(-11)+4536/72=4525/72